Immunochemical properties and cytochemical localization of the voltage- sensitive sodium channel from the electroplax of the eel (Electrophorus electricus) - Fritz, LC (J Neurosci, 1983)
Immunochemical methods have been used to investigate questions concerning the relatedness of sodium channels from different sources and their distribution in the eel electroplax. The reagents employed were two monoclonal antibodies, 5D10 (Moore, H. -P. H., L. C. Fritz, M. A. Raftery, and J. P. Brockes (1982) Proc. Natl. Acad. Sci. U.S.A. 79: 1673–1677) and 5F3, and a rabbit antiserum; all three were directed against determinants present on the 250,000-dalton component of the eel sodium channel. In quantitative adsorption assays, the three reagents were effectively adsorbed by eel electroplax membranes but not by brain membranes from rat, frog, or chick. The rabbit antiserum bound to immobilized membranes of rat brain at a level only approximately 0.1% of that seen with electroplax membranes. The reactivity of the three reagents with the eel electroplax was further investigated by indirect immunofluorescence on frozen sections. Whereas 5D10 showed no detectable reactivity, the rabbit antiserum and, especially, 5F3 stained the electrically excitable caudal face of the electrocytes but not the inexcitable rostral face. The reactivity of 5F3 was examined in greater detail and showed occasional abrupt discontinuities where the membrane was not stained. The presence of positive 5F3 immunoreactivity appeared to be correlated with extracellular filamentous material.